2017
DOI: 10.5455/apd.282536
|View full text |Cite
|
Sign up to set email alerts
|

The stigma perceived by parents of intellectual disability children: an interpretative phenomenological analysis study

Abstract: Objective: The aim of this is to put forth perceptions of the stigma that parents of intellectual disabled individuals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…The study highlights less support of mothers by their spouses who were always absent either due to work or failed relationships, leaving all parental responsibilities to mothers. Duran and Ergün [ 32 ] found that in Turkey mothers of children with ID were frequently in arguments with their spouses over the care of these children. Most participants were women and either single parents, divorced, widowed, or separated from their spouses, raising the children without support of their partners.…”
Section: Discussionmentioning
confidence: 99%
“…The study highlights less support of mothers by their spouses who were always absent either due to work or failed relationships, leaving all parental responsibilities to mothers. Duran and Ergün [ 32 ] found that in Turkey mothers of children with ID were frequently in arguments with their spouses over the care of these children. Most participants were women and either single parents, divorced, widowed, or separated from their spouses, raising the children without support of their partners.…”
Section: Discussionmentioning
confidence: 99%
“…This statement is also in line with another study by Butchner [27] on "society's attitude towards persons with disabilities" which found that society perceives that disability is a curse and punishment from ancestors and gods. Also, Duran and Ergun [28] in their study on "The stigma perceived by parents of children with disability: an interpretative phenomenological analysis study in Balikesir found that the majority of people often have negative perceptions and stigmatizing attitudes towards children with disabilities (CP) and their families. In the same study, it was found that parents of children with disabilities cope with insults and rude behaviors from community members while they struggle with the challenges of their children with CP.…”
Section: Parental Factorsmentioning
confidence: 99%
“…For working mothers, the stigmatised experiences would be more significant as they are subjected to an additional domain of environment, i.e., the workplace. As stigmatisation can lead the mothers to get more emotionally distressed, become isolated, and subsequently affect their caring roles in meeting the child's needs, the issue thus, warrants an urgency to address and intervene (Duran & Ergün, 2018).…”
Section: Workplace Stigmamentioning
confidence: 99%